Case report and literature review: fetal diagnosis of vascular ring with circumflex right aortic arch and unique aortic arch branching pattern - Langenfeld, Tyler; Ali, Yumna; Sharma, Chetan; Agarwal, Arpit (Frontiers in Cardiovascular Medicine, 2025)
Circumflex right aortic arch is a rare aortic arch anomaly where the arch extends in a retro-esophageal pattern with a left-sided descending thoracic aorta. In the setting of circumflex right aortic arch with the ductus arteriosus connecting the left descending aorta and left pulmonary artery, a vascular ring is present and can cause compressive symptoms of the aerodigestive tract. A 33-year-old G4P3 patient underwent fetal echocardiography after obstetric ultrasound showed concern for double aortic arch. Fetal echocardiogram was suspicious for vascular ring with presumptive diagnosis of double aortic arch vs. circumflex right aortic arch. The child was born at 38 weeks gestation via induced vaginal delivery and had an uneventful postnatal course. Post-natal echocardiogram was able to diagnose vascular ring but could not fully assess the arch or branching pattern. Cardiac computed tomography angiography (CCTA) was able to definitively diagnose right aortic arch and characterize the branching pattern. To our knowledge, this is the first case reported in the literature of a circumflex right aortic arch suspected on fetal echocardiogram and postnatal echocardiogram and subsequently confirmed with CCTA. Fetal echocardiogram provides a unique opportunity to assess the aortic arch as the trachea is filled with fluid. However, circumflex aortic arch and double aortic arch can be difficult to delineate on fetal or post-natal echocardiography. CCTA is an effective modality for evaluation of the aortic arch and its branching pattern in the setting of non-diagnostic echocardiography.